Perempuan dan Kesadaran Arti Pohon: Studi Kasus Etnobotani - Retnaningsih, Umi (Jurnal Ilmiah Hubungan Internasional, 2024)
The issue of global warming resulting from carbon emissions of greenhouse gas is a concern for nations inthe world including Indonesia. The Indonesian government has launched several programs for mitigation, including planting trees in urban areas. In 2007, Indonesia introduced Women Planting Trees and Management, WomenPlanting Trees Movements and Food Resilience Program (GPT-PKP), and other programs. Research explored theprogram implementation in Indonesia by collecting data and analyzing women's knowledge, perceptions, awareness,and actions for planting trees and their management. Surveys were conducted for data on the meaning of treessocially, economically, and environmentally. After completion surveys, the good participants were interviewed deeply and observed to prove their genuine awareness and action for planting and maintaining trees in their daily lives. Research revealed planting trees did not provide social and economic benefits. Trees taproots damaged walls and buildings, leaves made yards dirty, and lack of appreciation for being an environmentally friendly person by planting trees. Keywords: Awareness of trees, Indonesian government program, social and economic benefits, women,